O analiză descriptivă a conceptului de teologie - Zoltán Szallós-Farkas (TheoRhēma, 2014)
The study aims to give a definition of both the concept of “theology”, in general, and that of “Systematic Theology”, in particular. Such definitions have been reached by applying a descriptive analysis of the respective concepts within the framework of their etymology, scope and also from the perspective of how theological knowledge is achieved when one relies on the epistemological paradigm offered by the Gospel of John 17:3.